Remote monitoring of an object using a wireless sensor network based on NODEMCU ESP8266 - Hicham Ouldzira; Ahmed Mouhsen; Hajar Lagraini; Mostafa Chhiba; Abdelmoumen Tabyaoui; Said Amrane (Institute of Advanced Engineering and Science, 2019)
In recent years, wireless sensors networks (WSNs) have been imposed as an effective means of interconnection with simultaneous communication and information processing. They allow operating with sensors at low cost and low power consumption in various application areas such as ecosystem monitoring, detection and monitoring of objects and smart cities, etc.This paper describes the development of a system to detect the presence of an object and monitor it. This prototype is based on four NodeMcu modules (a static access point that provides the WIFI network, a server, a client and a mobile access point attached to the remote surveillance object) programmed under Arduino IDE and communicating between them via the HTTP protocol. The remote monitoring of the object for a linear disposition of the nodes used is based on the existence of the mobile access point in the HTTP client field.